Mapping the International Underground: Jeff Nuttall and Global Counterculture. Issue 1 (1st April 2017) - Field,
Abstract : Despite publishing nearly forty books between 1963 and 2003, Jeff Nuttall remains a minor figure in the history of the International Underground of the long 1960s. Drawing on his uncatalogued papers at the John Rylands Library, this article seeks to recoup Nuttall as one of the key architects of the International Underground. In so doing, my article argues that Nuttall's contributions to global counterculture challenge the critical consensus that British avant-garde writers were merely imitators of their US counterparts. By exploring the impact of Nuttall's My Own Mag (1963–67) and Bomb Culture (1968), it can be shown that Nuttall was a central catalyst of, and contributor to, the International Underground. As a poet, novelist and artist, Nuttall's multidisciplinary contributions to art were at the forefront of avant-garde practices that sought to challenge the perceived limitations of the novel as a social realist document and visual art as a medium confined to canvas.